The role of website format, blog use, and information-gathering acquaintance in online message assessment. Issue 4 (November 2015) - Greer, Jennifer; Pan, Po-Lin
Highlights: Examining effects of website format, blog use and information-gathering acquaintance. Websites with higher credibility do not activate better online message perceptions. Information-gathering acquaintance and website format jointly affect online message perceptions. Mutual effects of blog use and website format are found on online message perceptions. Blog use is less relevant to online message perceptions than information-gathering acquaintance. Abstract: By manipulating branded editorial, branded blog, and non-branded blog in a between-subjects experiment, this study examined online message perceptions in terms of credibility, quality, preference, and persuasiveness. The study explored whether website format, blog use, and information-gathering acquaintance would come into play when media users evaluated news information of various websites. Results suggested that the participants who evaluated websites as more credible did not translate into higher credibility ratings of the messages on the websites, nor did it lead to greater ratings of quality, preference, and persuasiveness. Additionally, information-gathering acquaintance and blog use were two crucial factors to online message perceptions. Both information-gathering acquaintance and blog use yielded joint effects with website format on online message perceptions. Moreover, blog use was found as less relevant to online message assessment than information-gathering acquaintance.